Design, synthesis and evaluation of novel oxazaphosphorine prodrugs of 9-(2-phosphonomethoxyethyl)adenine (PMEA, adefovir) as potent HBV inhibitors - Lu, Peng; Liu, Jiangxia; Wang, Yuya; Chen, Xiaoyan; Yang, Yushe; Ji, Ruyun (Bioorganic & medicinal chemistry letters, 2009)
A series of novel oxazaphosphorine prodrugs of PMEA is disclosed. l-valine methyl ester (7c) demonstrated highly potent anti-HBV activity, excellent stability in human plasma and release of the parent compound PMEA in human microsomes. A series of novel oxazaphosphorine prodrugs of 9-(2-phosphonomethoxyethyl)adenine (PMEA, adefovir) were synthesized and their anti-hepatitis B virus (HBV) activity was evaluated in HepG2 2.2.15 cells, with adefovir dipivoxil as a reference drug. In the cell assays, compounds 7b and 7d exhibited anti-HBV activity comparable to that of adefovir dipivoxil, while compound 7c, with an IC50 value of 0.12μM, was found to be three times more potent than the reference compound. In vitro stability studies showed that (SP,S)-7c, the diastereomer of compound 7c, was stable in human blood plasma but underwent rapid metabolism to release the parent drug PMEA in liver microsomes. The possible metabolic pathway of (SP,S)-7c in human liver microsomes was described. These findings suggest that compound (SP,S)-7c is a promising anti-HBV drug candidate for further development.